Broadband Photodetectors: Demonstration of a Broadband Photodetector Based on a Two‐Dimensional Metal–Organic Framework (Adv. Mater. 9/2020). Issue 9 (3rd March 2020) - Arora, Himani; Dong, Renhao; Venanzi, Tommaso; Zscharschuch, Jens; Schneider, Harald; Helm, Manfred; Feng, Xinliang; Cánovas, Enrique; Erbe, Artur
Abstract : In article number 1907063, Himani Arora, Enrique Canovas, Artur Erbe, and co‐workers demonstrate broadband photodetectors based on a novel π–d conjugated Fe3 (THT)2 (NH)3 2D metal–organic framework (MOF), operative in the UV‐to‐NIR range. Due to the small IR bandgap of the MOF, the photodetectors are best operated at cryogenic temperatures by suppressing the thermally activated charge‐carrier population. Thus, a proof‐of‐concept MOF photodetector is reported, revealing MOFs as promising candidates for optoelectronics.